Classroom Instruction that Works with English Language Learners Participant's Workbook - Hill, Jane D; Bjork, Cynthia Linnea (Association for Supervision and Curriculum Development, 2008)
Everyone who participates in your workshop on "Classroom Instruction That Works with English Language Learners" needs this participant's workbook to gain expertise in strategies that are effective with ELL (English Language Learners) students.